If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2 = -4y + -12 Reorder the terms: 2 + 3y = -4y + -12 Reorder the terms: 2 + 3y = -12 + -4y Solving 2 + 3y = -12 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 2 + 3y + 4y = -12 + -4y + 4y Combine like terms: 3y + 4y = 7y 2 + 7y = -12 + -4y + 4y Combine like terms: -4y + 4y = 0 2 + 7y = -12 + 0 2 + 7y = -12 Add '-2' to each side of the equation. 2 + -2 + 7y = -12 + -2 Combine like terms: 2 + -2 = 0 0 + 7y = -12 + -2 7y = -12 + -2 Combine like terms: -12 + -2 = -14 7y = -14 Divide each side by '7'. y = -2 Simplifying y = -2
| -1=.5a+9 | | n/7=9/4 | | a/9=a-4/5 | | 0.10(x+80)+0.90x=33 | | -[-10x-4]=4x+14 | | 10x-43-8x=13 | | http://media.apexlearning.com/Images/201305/30/4690173e-3b40-45a8-b981-16fc638a0743.gif | | 3m+35=8m+15 | | 15/7 | | 167+19t+16t=1132 | | -2x+16=30+3x | | 8y-6=2y+24 | | -4=12/20-5 | | 5k-15=25 | | 3(7-2z)=14-8(z-1) | | 1=5=1x/6 | | 8-5t=t-16 | | 6y-3=9y-4y | | 5k-(2k-10)=25 | | 14.50-p=53.00 | | 3(2c+5)=39 | | -(3k+4)=6k-3(3k+2) | | 15m+20=8m-22 | | 6x-3y=8x+10 | | 7+8x+2x=7 | | 48x^2-58x+15=0 | | 6x+16=4x-10 | | X^2+X+1-i=0 | | 37+8x=(7-x) | | X=(13/5)*y | | X=(13/5)×y | | 14=.5(8x+12) |